Population sequencing for phylogenetic diversity and transmission analyses - Talima Pearson; Tara Furstenau; Colin Wood; Vanessa Rigas; Kylie Drake; Jason Sahl; Sara Maltinsky; Bart J. Currie; Mark Mayo; Carina Hall; Paul Keim; Viacheslav Fofanov (Proceedings of the National Academy of Sciences, 2025)
Genomic diversity in pathogen populations is foundational for evolution and adaptation. Understanding population-level diversity is also essential for tracking sources and revealing detailed pathways of transmission and spread. For bacteria, culturing, isolating, and sequencing the large number of individual colonies required to adequately sample diversity can be prohibitively time-consuming and expensive. While sequencing directly from a mixed population will show variants among reads, they cannot be linked to reveal allele combinations associated with phylogenetic inheritance patterns. Here, we describe the theory and method for using population sequencing directly from a mixed sample, along with a minimal number of individually sequenced colonies, to describe the phylogenetic diversity of a population without haplotype reconstruction. To demonstrate the utility of population sequencing in capturing phylogenetic diversity, we compared isogenic clones to population sequences of Burkholderia pseudomallei from sputum of a single patient. Our results point to the pathogen population being highly structured, suggesting that for some pathogens, sputum sampling may preserve structuring in the lungs and thus present a noninvasive alternative to understanding colonization, movement, and pathogen/host interactions. We also analyzed population sequences of Staphylococcus aureus derived from different people and different body sites to reveal directionality of transmission between hosts and across body sites, demonstrating the power and utility for characterizing the spread of disease and identification of reservoirs at the finest levels. We anticipate that population sequencing and analysis can be broadly applied to accelerate research in a wide range of fields reliant on a foundational understanding of population phylogenetic diversity.